Hebrew gothic: history and the poetics of persecution - Grumberg, Karen (Jewish literature and culture, 2019)
Introduction: Gothic Matters -- Always Already Gothic: S. Y. Agnon's Tales of Terror and the Spectral European Jewish Past -- Maternal Macabre: Feminine Subjectivity at the Edge of the Shtetl in Dvora Baron and Jacob Steinberg -- After the Nightmare of the Holocaust: Gothic Temporalities and the Insecure Sanctuary in Lea Goldberg's "The Lady of the Castle" and Edgar Allan Poe's "The Masque of the Red Death" -- Dark Jerusalem: Amos Oz's Anxious Literary Cartography Between 1948 and -- Historiographic Perversions: Echoes of Otranto in A. B. Yehoshua's Mr. Mani -- A Séance for the Self: Memory, Non-Memory and the Re-Orientation of History in Almog Behar and Toni Morrison -- Coda: "Here are our monsters": Hebrew Horror from the Political to Pop